1989
DOI: 10.1029/jd094id02p02171
|View full text |Cite
|
Sign up to set email alerts
|

Electrical structure in two thunderstorm anvil clouds

Abstract: Two electric field soundings through thunderstorm anvil clouds show similar charge structures: negatively charged screening layers on the top and bottom surfaces, a layer of positive charge in the interior, and one or two layers of zero charge. Both anvil clouds were strongly electrified: the peak magnitudes of the electric field in the two storms were 70 and 90 kV/m, respectively. The nonzero layers had charge densities comparable to those found in the cores of thunderstorms, ranging in magnitude from 0.4 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 13 publications
6
78
0
Order By: Relevance
“…Measurements of electric field inside the anvils of thunderstorms have been made by Marshal et al (1989); Byrne et al (1989); Stolzenberg et al (2004); Dye and Willet (2007); and Merceret et al (2008) using balloon and aircraft platforms. Balloon measurements by Marshall et al (1989) in New Mexico and Oklahoma using an electric field meter (EFM) found a rapid change in electric field at the lower boundary of the anvil cloud, suggesting a layer of charge present at the cloud edge. The change in electric field was81kVm -1 over a vertical distance of 1.1km, and the derived space charge ρ = -0.7nCm…”
Section: Anvilsmentioning
confidence: 99%
“…Measurements of electric field inside the anvils of thunderstorms have been made by Marshal et al (1989); Byrne et al (1989); Stolzenberg et al (2004); Dye and Willet (2007); and Merceret et al (2008) using balloon and aircraft platforms. Balloon measurements by Marshall et al (1989) in New Mexico and Oklahoma using an electric field meter (EFM) found a rapid change in electric field at the lower boundary of the anvil cloud, suggesting a layer of charge present at the cloud edge. The change in electric field was81kVm -1 over a vertical distance of 1.1km, and the derived space charge ρ = -0.7nCm…”
Section: Anvilsmentioning
confidence: 99%
“…Negative charge was located between 5.2 and 5.8 km [e.g., Stolzenburg et al, 1998c]. Above 5.8 km, it is more difficult to identify the charge regions, except for the uppermost positive charge between 7.3 and 7.7 km, which seems to be a screening charge at the upper cloud boundary [e.g., Marshall et al, 1989;Marshall and Rust, 1991]. Positive charge tended to dominate between 5.8 and 7.3 km, but was interspersed with negative and apparent neutral charge regions.…”
Section: Flash Amentioning
confidence: 99%
“…Such lightning often propagates along cloud base and is called "spider lightning" [Marshall et al, 1989;Mazur et al, 1995Mazur et al, , 1998]. …”
Section: Introductionmentioning
confidence: 99%